Pengembangan Bahan Ajar Interaktif Berbasis Media Sosial Schoology - Latifah, Sri; Utami, Ardini (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract:This study aims:(1) to find out the feasibility of interactive physics teaching materials based on schoology social media, (2) to find out theresponse of students to the attractivenessinteractive physics teaching materials based on schoology social media that has been developed. This study is a Research andDevelopment (R and D) using Borg and Gall’s procedure. This research was carried out at SMAYP UnilaBandar Lampung, SMA N1 Bukit Kemuning, andSMA N 7 Bandar Lampung with research objects were students of class XI. The results of the validation from material experts, media experts and technology experts showed very decent results with the presentations reaching 83.25%. Then the teaching materials were tested through 2 steps, namely small trials and field trials. The average results obtained were 84,93% for small group trials and 81.29% for field trials at SMA YP Unila Bandar Lampung, SMA N 1 Bukit Kemuning andSMA N 7 Bandar Lampung, so interactive physics teaching materials based on social media schoology from the three schools has very interesting criteria.Abstrak:Penelitian ini bertujuan untuk:(1) mengetahui kelayakan bahan ajar fisika interaktif berbasis media sosial schoology,(2) mengetahui respon peserta didik terhadap kemenarikan bahan ajar fisika interaktif berbasis media sosial schoology yang telah dikembangkan.Penelitian ini merupakan penelitian pengembangan atau Research and Development (R and D) dengan menggunakan prosedur Borg and Gall. Penelitian ini dilaksanakan di SMA YP Unila Bandar Lampung, SMA N 1 Bukit Kemuning, danSMA N 7 Bandar Lampung dengan objek penelitian adalah peserta didik kelas XI.  Hasil validasi dari ahli materi, ahli media dan ahli teknologi menunjukkan hasil sangat layak dengan presentasi mencapai 83,25%.Kemudian bahan ajar di uji coba melalui 2 tahap yaitu uji coba kecil dan uji coba lapangan. Hasil rata-rata yang diperoleh yaitu 84,93% untuk uji coba kelompok kecil dan 81,29% untuk uji coba lapangan di SMA YP Unila Bandar Lampung, SMA N 1 Bukit Kemuning dan SMA N 7 Bandar Lampung, sehingga bahan ajar fisika interaktif berbasis media sosial schoology dari ketiga sekolah tersebut memiliki kriteria sangat menarik.